Transformasi Pendidikan Kebencanaan di Sekolah Dasar melalui Virtual Disaster Simulation: Upaya Penguatan Literasi Bencana - Bachri, Syamsul; Hidiyah, Tabita May; Hakiki, A. Riyan Rahman; Putri, Nanda Regita Cahyaning; Prastiwi, Mellinia Regina Heni (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2025)
Early disaster literacy is essential in fostering preparedness among elementary school students, particularly in disaster-prone areas such as the vicinity of Mount Raung. However, disaster education in schools is often limited to conventional approaches that fail to fully engage young learners. This community service program aimed to enhance students’ knowledge and preparedness at SDN 3 Jambewangi through an educational initiative based on Virtual disaster simulation. The program was implemented in three main phases: preparation, implementation, and evaluation. During the implementation phase, students received basic disaster knowledge and participated in virtual simulations using Virtual Reality (VR) technology that depicted interactive disaster scenarios. The results demonstrated significant improvements in students’ understanding of disaster concepts, active engagement during simulation sessions, and their ability to articulate mitigation procedures independently. In addition, the project included the installation of evacuation routes and assembly points within the school environment as a form of infrastructure support. Overall, this program successfully provided an immersive and contextual learning experience, while strengthening the school’s preparedness system in facing potential natural disasters.